Sport and religion: a mapping analytical research - Sofyan, Davi; Abdullah, Khairul Hafezad; Osiobe, Ejiro Uriri; Indrayogi, Indrayogi; Rusdiyanto, Rajip Mustafillah; Gazali, Novri; Samodra, Yohanes Touvan Juni (Intelektual Pustaka Media Utama, 2023)
This study uses scientometric analysis to comprehensively describe the descriptive parameters of publications about the relationship between sport and religion. Using ScientoPy, VOSviewer, and Biblioshiny software and datasets from two leading academic databases, Scopus and Web of Science, the current study can identify the most active scientific sources, keywords, and trending topics in sports and religion research. According to the findings, numerous types of research have been carried out on the correlation between sports and religion, and most of these papers have been published by scholars from the United States. The International Journal of the History of Sport and Sport in society has become the most active scientific journal. Furthermore, this study emphasizes the frequently utilized terms in the literature, explicitly